Affected : Emotionally Engaging Customers in The Digital Age - Wrigley, Cara; Straker, Karla (John Wiley & Sons Australia, Ltd, 2018)
How can you create meaningful connections with customers in the digital space'' The rapid emergence of new technologies has revolutionized the way companies build relationships and interact with their customers. Today, it's more important than ever to have an emotional understanding of customers and how they feel about a product, service, or business, even when your primary interactions are via digital channels.' Affected goes beyond influencing behaviors to understanding cognition and emotion as a way to better connect with customers in the digital space. In it, Wrigley and Straker offer a new approach'one that examines channel relationships and useful concepts for clarifying and refining the emotional meaning behind company strategy and their relationship to corresponding channels. Using case study examples from and over a decade of primary research in the area, they discuss the process and impact of such emotionally aware channel designs. Spanning entrepreneurial start-up techniques of wunderkind artist Cj Hendry through to the lucrative retail sector of luxury brand Burberry, this seminal book offers multi-channel design approach that can show companies how to select, design, and maintain digital engagements based on their strategy and industry needs.-Shows businesses how they can better understand and engage with customers digitally -Demonstrates how to gain competitive advantage by integrating design methods into corporate strategy -Provides multi-channel approaches for how businesses can select, design, and maintain digital engagements -Establishes a clear framework for analysing and applying the right strategy for your digital engagement' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' ' Connecting and engaging with customers is pivotal to business success, but in the digital space the old methods just won't cut it. With Affected, you'll find the tools and techniques you need to find your customers where they are.